1867. Characteristics and Outcomes of Patients with SARS-CoV-2 Reinfections Requiring Treatment in a COVID-19 Ambulatory Treatment Program. (15th December 2022) - Cowman, Kelsie; Golia, Austin; Guo, Yi; McSweeney, Terrence D; Chang, Mei H; Bao, Hongkai; Nori, Priya
Abstract: Background: Montefiore Medical Center (MMC), Bronx, NY, established an ambulatory program to offer COVID-19 treatments (monoclonal antibodies [mAB] and oral antivirals) to patients with mild-moderate illness according to emergency use authorization criteria. Given multiple pandemic waves in the area, several patients have been reinfected and were treated twice. The objective of this analysis is to identify clinical characteristics and outcomes in patients with repeated COVID-19 infections and treatments. Methods: Electronic health records were reviewed to identify patients between December 1, 2020 and April 28, 2022 who received COVID-19 treatment on more than one occasion at MMC. Data collected included demographics, risk factors for progression to severe illness, name and date of COVID-19 treatments received, vaccination status, and clinical outcomes of 30-day emergency department (ED) presentation or hospital admission following each treatment. Results: Out of 3, 042 total treated patients, 13 (0.4%) received multiple treatments with either mAB or oral antivirals for COVID-19 reinfection during the study period. Median age of reinfected patients requiring treatment was 50 years. Median days between first and second treatments was 298 days (range 91-468 days). The most common risk factor for progression to severe disease were cardiovascular disease (54%) and immunocompromised status (62%) (Table 1). Ten patients had received at least two doses of vaccine (77%) with Pfizer (54%) or Moderna (23%) vaccines prior to reinfection. No patients reported any adverse reactions to either treatment. Four patients presented to the ED or were hospitalized following treatment of reinfection, three of which were for COVID-related symptoms. Of these, two had two risk factors for progression and the third had been hospitalized previously for initial COVID-19 infection. Conclusion: Though COVID-19 reinfection has been described, especially during Omicron surges, there were relatively few reinfected patients requiring treatment in our cohort. Patients with risk factors for disease progression may also be at increased risk for reinfection, especially the immunocompromised. Disclosures: Kelsie Cowman, MPH, Merck: Grant/Research Support Yi Guo, PharmD, BCIDP, Merck: Grant/Research Support.